A field‐applicable method for flow cytometric analysis of granulocyte activation: Cryopreservation of fixed granulocytes. Issue 5 (13th March 2018) - de Ruiter, Karin; van Staveren, Selma; Hilvering, Bart; Knol, Edward; Vrisekoop, Nienke; Koenderman, Leo; Yazdanbakhsh, Maria
Abstract: Upon activation granulocytes upregulate several adhesion molecules (CD11b) and granule proteins (CD35, CD66b) and shed surface l ‐selectin (CD62L). These changes in expression, as assessed by flow cytometry, can be used as markers for activation. Whereas these markers are usually studied in fresh blood samples, a new method is required when samples are collected at a field site with no direct access to a flow cytometer. Therefore, we developed and tested a field‐applicable method in which fixed leukocytes were cryopreserved. Using this method, the intensity of granulocyte activation markers was compared to samples that were either stained fresh, or fixed prior to staining but not cryopreserved. In addition, the response to an in vitro stimulation with fMLF was determined. While we observed differences in marker intensities when comparing fresh and fixed granulocytes, similar intensities were found between fixed cells that had been cryopreserved and fixed cells that did not undergo cryopreservation. Although fixation using FACS lysing solution might lead to membrane permeabilization, activation markers, and the responsiveness to fMLF or eotaxin could still be clearly measured. This method will, therefore, enable future studies of granulocyte activation in settings with limited resources and will allow simultaneous analysis of samples collected at different time points. © 2018 International Society for Advancement of Cytometry Abstract :